2021
DOI: 10.1007/s00395-021-00881-9
|View full text |Cite
|
Sign up to set email alerts
|

Small extracellular vesicles obtained from hypoxic mesenchymal stromal cells have unique characteristics that promote cerebral angiogenesis, brain remodeling and neurological recovery after focal cerebral ischemia in mice

Abstract: Obtained from the right cell-type, mesenchymal stromal cell (MSC)-derived small extracellular vesicles (sEVs) promote stroke recovery. Within this process, microvascular remodeling plays a central role. Herein, we evaluated the effects of MSC-sEVs on the proliferation, migration, and tube formation of human cerebral microvascular endothelial cells (hCMEC/D3) in vitro and on post-ischemic angiogenesis, brain remodeling and neurological recovery after middle cerebral artery occlusion (MCAO) in mice. In vitro, sE… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
98
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 115 publications
(99 citation statements)
references
References 42 publications
0
98
0
1
Order By: Relevance
“…the MSC source, cell culturing conditions, and sEV preparations [12,16]. Only by thorough characterization of both the MSCs and their sEVs, the quality of MSC-sEV preparations can be assured.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…the MSC source, cell culturing conditions, and sEV preparations [12,16]. Only by thorough characterization of both the MSCs and their sEVs, the quality of MSC-sEV preparations can be assured.…”
Section: Discussionmentioning
confidence: 99%
“…Ischemic stroke mainly affects aged humans. Importantly, the effects of MSC-sEVs have so far been evaluated in young, mostly otherwise healthy rats and mice [1,2,4,[10][11][12][13][14][15][16][17][18]. To date, MSC-sEV effects on stroke recovery have not yet been assessed in aged rodents.…”
Section: Introductionmentioning
confidence: 99%
“…Because EVs are not live cells, the low efficacy of MSC therapy due to poor survival can be overcome by the MSC-EVs therapy. Many studies have reported that the local injection of EVs secreted by human MSCs from different sources can promote angiogenesis, suggesting that EV-based therapy is a promising treatment [ 8 ].…”
Section: Introductionmentioning
confidence: 99%
“…One important finding of the study is the interest in using EVs from IFNγ pre-activated MSCs to enhance their beneficial effect in the lungs of SSc mice. It has already been shown that MSC priming by hypoxia or genetic modification may enhance their therapeutic properties in other applications [19,20]. Improvement of fibrotic, remodeling and inflammatory markers was observed by comparison with EVs from non-activated MSCs.…”
Section: Discussionmentioning
confidence: 95%